Multiobjective automated and autonomous intelligent load control for smart buildings - Ashabani, Mahdi (2020)
This paper deals with design of a real-time and versatile yet simple control and management strategy for provision of adaptive and intelligent demand response for buildings. The proposed three-phase multiobjective autonomous/automated intelligent load (MAIL3) control strategy offers the following superiorities in a computationally-efficient approach: 1) by introducing voltage hopper technology, it can provide autonomous and automated grid ancillary service and load control without the need for a supervisory/centralized controller; 2) it can also track and realize regulation commands from an independent system operator; 3) it is applicable to buildings with hybrid AC/DC grids including AC and DC impedance loads, battery energy storage systems (BESSs), and variable frequency drives (VFDs); 4) it is a unified load control strategy for both grid-connected and islanded buildings with seamless transition between them; 5) as opposed to common on/off demand control techniques in the literature, the proposed method provides a continuous and adaptive demand control; and 6) the MAIL3 is based on a new control technique for voltage source converters using synchronous current converters technology. Extensive results are presented to demonstrate effectiveness of the method.